AGAMA DAN FILANTROPI: PENGARUH PROMOSI TERHADAP MINAT MASYARAKAT MENJADI FILANTROPIS ZAKAT (MUZAKKI) PADA LEMBAGA AMIL ZAKAT DI KOTA AMBON - Rosna Kurnia; Dety Aryani Relubun; Wahyu Ismail Kurnia; Roni Ismail (Religi: Jurnal Studi Agama-agama, 2020)
Each religion obliges its followers to do philanthropy deed. Zakat is one of philanthropy tenets in Islam. In Islam, zakat is believed to be one of the vital instruments in an effort to eradicate poverty, decrease unemployment rate, and improve the life quality of society. As Muslim majority country, Indonesia rightly need to optimize the zakat philanthropy program through stimulating people's inclination to become loyal zakat philanthropist or Muzakki in one of the Zakat collection agencies in Indonesia. This research, therefore, is aiming at analyzing the influence of promotion on forming people's interest in becoming Muzakki in one of the Zakat agencies in Ambon, Maluku province. The quest was particularly conducted in YAKESMA Zakat Agency in Ambon. The data collection processes were literary study, interview, and questionnaire allotment regarding the research. As for the data analyzing, the simple linear regression analysis was used with variables consisting of promotion scale and people's proclivity of 25 out of 154 respondents. The outcome of the research indicated that the promotion scale has a significant improvement of people's proclivity to become Muzakki or zakat philanthropist in YAKESMA Zakat agency in Ambon. The promotion effort contributed 78.9 percent in forming Ambonese’s proclivity to become loyal zakat philanthropist (Muzakki) in YAKESMA Zakat agency in Ambon.